Fabrication of Nanosize Films on the Base of Scutterudite CoSb₃ for Thermoelectric Devices - Makogon, Yu.M.; Sidorenko, S.I.; Shkarban, R.A. (Успехи физики металлов, 2018)
The work is concerned with ascertainment of the regularities for thermostimulated formation of the phase composition and structure of CoSb₃-scutterudite-based films deposited by the vacuum condensation method as well as the effect of the nanoscale factor on their thermoelectric properties.